Soil Characteristic Comparison of Fenced and Grazed Riparian Floodplain Wetlands in the Typical Steppe Region of the Inner Mongolian Plateau, China - Lixin Wang; Huamin Liu; Yuhong Liu; Jianwei Li; Hongbo Shao; Wei Wang; Cunzhu Liang (The Scientific World Journal)
In recent decades, degradation of ecosystem in the steppe region of the Inner Mongolia Plateau, especially in riparian floodplain wetlands, has become a significant ecological crisis. Not uncommonly, with the increasing of livestock in the Inner Mongolian steppe region, a riparian floodplain wetland is becoming a hotspot area of grazing for local herdsmen. Hence, it is essential to understand degradation mechanisms of riparian floodplain wetland ecosystems caused by extensive grazing. In this study, the spatial distribution of soil compaction, salinity, total nitrogen, total phosphorus, organic carbon, and microbial biomass C and N were investigated. The results showed that grazing led to an increase in soil compaction and soil surface salinity, which significantly lowered levels of total N, P, and TOC in the soil surface. Grazing decreased soil microbial biomass C and N concentration in the lower riparian floodplain wetland, whereas it significantly increased soil microbial biomass C and N concentration in the higher riparian floodplain wetland. Elevation differences in the riparian floodplain wetland increased spatial heterogeneity in the soil and thus resulted in different influence of grazing on wetland soils and ecosystem. Therefore, elevation differences and grazing intensity were the main factors controlling soil characteristics in the riparian floodplain wetland of this region.